Micro-gun based on laser pulse propulsion. Issue 1 (December 2017) - Yu, Haichao; Li, Hanyang; Cui, Lugui; Liu, Shuangqiang; Yang, Jun
Abstract This paper proposes a novel "micro-gun" structure for laser pulse propulsion. The "micro-bullets" (glass microspheres) are irradiated by a laser pulse with a 10 ns duration in a dynamic process. Experimental parameters such as the microsphere diameter and the laser pulse energy are varied to investigate their influence on laser pulse propulsion. The energy field and spatial intensity distribution in the capillary tube were simulated using a three-dimensional finite-difference time-domain method. The experimental results demonstrate that the propulsion efficiency is dependent on the laser pulse energy and the microsphere size. The propulsion modes and sources of the propelling force were confirmed through direct observation and theoretical calculation. Waves also generated by light-pressure and thermal expansions assisted the propulsion.